In Vivo High-Frequency Ultrasound for the Characterization of Thrombi Associated with Aortic Aneurysms in an Experimental Mouse Model - Jansen, Christian H. P.; Brangsch, Julia; Reimann, Carolin; Adams, Lisa; Hamm, Bernd; Botnar, Rene M.; Makowski, Marcus R. (Ultrasound in Medicine and Biology, 2017)
The development of abdominal aortic aneurysm (AAA) associated thrombi plays an important role during the onset and progression of AAAs. The aim of this study was to evaluate the potential of high-frequency ultrasound for characterization of AAA associated thrombi in an apolipoprotein-E-deficient mouse-model. Ultrasound measurements were performed using a high-resolution ultrasound system (Vevo770, FUJIFILM VisualSonics, Inc., Toronto, ON, Canada) with a 30 MHz linear-array transducer (RMV707 B). Magnetic resonance imaging with a 3 Tesla scanner (Achieva MR system, Philips Healthcare, Best, The Netherlands) and a single-loop microscopy coil was performed as a reference standard. All stages of aneurysm development were evaluated by histologic analyses. The “signal-thrombus-matrix” to “signal-blood” ratio on high-frequency ultrasound measurements showed a strong correlation (R2 = 0.81, p < 0.05) with the state of extracellular matrix remodeling. Furthermore, size measurements derived from the high-frequency ultrasound correlated well with magnetic resonance imaging and histology. This study demonstrated that high-frequency ultrasound enables the reliable in vivo quantification of extracellular matrix remodeling at various stages of thrombus development, based on the thrombus echogenicity.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Abdominal aortic aneurysms; Magnetic resonance imaging; Ultrasound